Tinjauan Literatur: Kepatuhan Orangtua Dalam Menerapkan Perilaku Sehat Untuk Mencegah Penularan Penyakit Pada Anak - Nastasya, Ricca Olivia; Wanda, Dessie (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2021)
Introduction: Transmission of the disease can occur to anyone, but children are very susceptible to infection and can cause morbidity and mortality in children. The most commonly transmitted infectious diseases such as respiratory infections and gastrointestinal infections. Parents are role models for children. Healthy behavior in parents can affect children. Increased knowledge, attitudes can change behavior leading to health is applied by practicing hand hygiene, keeping children away from crowds, and wearing masks. Objectives: The purpose of this literature is to identify parental compliance in implementing healthy behaviors to prevent disease transmission in children. Methods: The method used is a literature review. Results: The results obtained are 6 literatures that have been analyzed, namely parental compliance, the influence of knowledge, attitudes towards preventing disease transmission; mother's healthy behavior affects children's health; health support facilities; health protocols; and risk factors. The conclusion of this literature review is the healthy behavior of parents by knowledge, attitudes, and behavior in preventing disease transmission. Recommendation: Recommendations from this literature review are the support of related institutions that are supported by facilities for implementing healthy behavior in parents. Providing information can add knowledge to change attitudes and practices for the better to prevent disease transmission in children. Health officials and related facilities can cooperate with local areas to provide health promotion.